THE BEST METHODS OF TEACHING ENGLISH AS A SECOND LANGUAGE - Sa'dullayeva Sitora Jamoliddin qizi; Karimov Ulugʻbek Nusratovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: A foreign language is a language that is not the native language of people. A person can learn a foreign language only through study - in schools, language courses and self-taught ways l - or through play as a child living in a foreign language area.It is important to know at least one foreign language at work and anywhere.